Occurence of the Hindgut Ciliates Paraisotricha colpoidea and P. minuta (Ciliophora: Paraisotrichidae) in Horses in Turkey - Gürelli, Gözde; Göçmen, Bayram (Galenos Yayinevi, 2012)
The aim of this study was to determine the cytological features of 2 endocommensal ciliates, P. colpoidea and P. minuta belonging to genus Paraisotricha found in the hindgut of 15 Turk rahvan and 15 English and Arabic horses from Izmir, compare the morphological characters of species with their original descriptions and previous reports and discuss the similarities and differences.The cytological features of two endocommensal ciliates were investigated with the pyridinated silver carbonate impregnation and silver nitrate impregnation techniques at the level of light microscopy.Specimens from our horses were found to be similar to the original descriptions on the basis of cytological features, morphological characters and biometric data.We have concluded that the geographical variation and feeding habits of the host animals are important for evaluating the biometric data of species.
Keywords: Turkey; Trichostomatida; Animals; Ciliophora Infections; Horse Diseases; Horses; Intestine, Large; Intestinal Diseases, Parasitic